Exploring Language as a Tool for Confidence and Empowerment in Public Discourse: A Transitivity Analysis of Muniba Mazari’s Speech “Be Confident, Be You” - Irsa Shafique; Maham Noor; Nimra Saud (Indus Journal of Social Sciences, 2025)
This study is aimed at identifying transitivity patterns in the speech “Be confident, Be you” by Muniba Muzari (2021). The author, via her speech text, both motivates her audience and shares her personal journey, leading to find an inner strength within her imperfections. The objective of the attempted study tries to examine how the source text focuses on individualism over collective support. In this respect, the language of the speech text is thoroughly explored to understand how the author used it as a device, mustering up confidence and supporting women empowerment in public discourse by challenging stereotypical roles socially assigned to women. The research study is conducted from the Transitivity Metafunction outlook, proposed by M.A.K Halliday (1985) under Systemic Functional Grammar (SFG) in the book titled “An Introduction to Functional Grammar” (1st edition, 1985). The applied method adopts qualitative paradigm of study by implying close reading technique and purposive sampling. Overall, the unfolding of the attempted study results in a discursive understanding of the source study text. At the end, definite recommendations are attached for future researchers interested in applying other metafunctions of the SFG methodology on the same text.